PENGARUH KITOSAN PADA EDIBLE FILM DARI KULIT SINGKONG TERHADAP KUAT TARIK DAN BIODEGRADASI EDIBLE FILM - vira maryati; Indang Dewata (Universitas Negeri Padang, 2021)
Edible film is a plastic that has a thickness of less than 0.25 mm and functions as a wrapper for food products. This study aims to determine the effect of adding chitosan to edible films made from cassava peel starch on the tensile strength and biodegradation of edible films. Variations in the concentration of chitosan added were 0%, 0.5%, 1%, 1.5% and 2%. Based on the results of the analysis that has been carried out, it is obtained data that the addition of chitosan affects the tensile strength and biodegradation of the edible film. The maximum tensile strength value was obtained with the addition of 1% chitosan of 14.91 Mpa. Biodegradation of edible film decreases with the addition of chitosan. Edible film without the addition of chitosan has a biodegradation value of 55.64%, while the edible film with the addition of 0.5%, 1%, 1.5%, and 2% chitosan has a biodegradation value of 43.72%, 24.15%, 17.61% and 10.98%. The tensile strength value obtained has met the standard value of JIS Z1707 edible film.